Brent Goose population studies, 1960-61 - Burton, P J K (Wildfowl, 1962)
The numbers of Dark-bellied Brent Branta b. bernicla wintering in England in 1960-61 were the highest for at least ten years. The total population of this subspecies in Europe was between 21,000 and 26,000. The number of Pale-bellied Brent B. b. hrota wintering in Ireland was nearly 12,000 and there were at least another 7000 of this form on the North Sea coasts of Europe. The Dark-bellied population had had a good breeding year in 1960, the proportion of young birds being about 45% in Essex and similarly high elsewhere in England and in Holland and France. The Irish Pale-bellied stock also included many young birds.